Preparation method of composite microcrystalline graphite particles and isostatic pressing graphite thereof

By preparing composite microcrystalline graphite particles with controllable pore structure, filling the pores of microcrystalline graphite with an impregnating agent, and combining specific process steps, the deficiencies of domestically produced isostatic graphite in terms of flexural strength and thermal conductivity have been solved, realizing the preparation of high-performance isostatic graphite to meet the needs of nuclear engineering.

CN119263835APending Publication Date: 2025-01-07HUNAN UNIV

Patent Information

Application Number
CN202411611771.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing domestically produced isostatic graphite has shortcomings in terms of high purity, high strength, and low coefficient of thermal expansion. In particular, microcrystalline graphite-based isostatic graphite has low flexural strength and low thermal conductivity, which makes it difficult to meet the needs of the nuclear engineering field.

Method used

By preparing composite microcrystalline graphite particles with controllable pore structure, filling the pores of microcrystalline graphite with an impregnating agent, and combining specific process steps such as kneading, calcination and graphitization, high-performance isostatic graphite is formed.

Benefits of technology

It significantly improves the flexural strength and thermal conductivity of microcrystalline graphite-based isostatic graphite while maintaining a low coefficient of thermal expansion, meeting the performance requirements of the nuclear engineering field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263835A_ABST
    Figure CN119263835A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of composite microcrystalline graphite particles and isostatic pressing graphite thereof. The preparation method comprises the following steps: step 1, preparing microcrystalline graphite particles; 2, preparing filled composite microcrystalline graphite particles; step 3, mixing, kneading and secondary crushing; step 4, forming and roasting; and step 5, graphitizing. According to the method, controllable pore filling is realized by dipping the microcrystalline graphite before mixing and kneading, so that the porosity of the microcrystalline graphite is reduced, and the average pore size is reduced, and therefore, the buffering effect of pores on thermal expansion in the c-axis direction of the graphite is retained while the strength of microcrystalline graphite particles is increased; therefore, the prepared microcrystalline graphite-based isostatic pressing graphite keeps a lower thermal expansion coefficient while the mechanical energy is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention relates to the field of isostatically pressed graphite materials, and in particular to a method for preparing composite microcrystalline graphite particles and isostatically pressed graphite. Background technology:

[0002] Isostatic graphite is a new type of carbon graphite material developed in the 1960s. It has the properties of high temperature resistance, corrosion resistance, high strength, good electrical and thermal conductivity, self-lubrication, low thermal expansion coefficient and good strength even at high temperatures. It is widely used in high-tech fields such as machinery, chemical industry, electronics, aerospace and nuclear industry, and is also known as one of the most valuable new materials in the 21st century.

[0003] In the field of nuclear engineering, carbon atoms have a large neutron scattering cross section and a small absorption cross section. When in the form of graphite, they have a high density and good physical and mechanical properties, making them a good moderation, reflection and structural material. This graphite is also called nuclear graphite. Usually, nuclear graphite is required to have high density, high strength, high purity, high isotropy, low thermal expansion coefficient and other characteristics to ensure the safety and stable operation of nuclear reactors. Therefore, isostatic graphite with the above characteristics has become the first choice for nuclear graphite.

[0004] Domestic isostatic graphite is usually made from petroleum coke and asphalt coke, and coal tar as a binder. It is prepared through process steps such as mixing, crushing, molding, roasting and graphitization. It still has problems such as high thermal expansion coefficient, low isotropy and low purity.

[0005] In recent years, Tsinghua University (CN200910023729X) and Hunan University have developed an isotropic graphite preparation technology using natural microcrystalline graphite as raw material. Studies have shown that microcrystalline graphite grains are isotropic and have the characteristics of high purity, high graphitization degree, low thermal expansion coefficient, etc. Therefore, the microcrystalline graphite-based isostatic graphite prepared therefrom has the characteristics of high isotropy and low thermal expansion coefficient. However, due to the low strength of the microcrystalline graphite aggregate itself, the flexural strength of the microcrystalline graphite-based isostatic graphite is relatively low, not exceeding 30MPa. In addition, due to the small size of the graphite crystallites inside the microcrystalline graphite particles, a relatively strong phonon-interface scattering will be produced, resulting in a low thermal conductivity of the microcrystalline graphite-based isotropic graphite, with a room temperature thermal conductivity of only 70-80W / mK. Summary of the invention:

[0006] In order to solve the above problems, the present invention provides a composite microcrystalline graphite particle with controllable pore structure and a method for preparing high-performance isostatic graphite.

[0007] The technical solution of the present invention is:

[0008] A method for preparing microcrystalline graphite-based isostatically pressed graphite comprises the following steps:

[0009] Step 1: Preparation of microcrystalline graphite particles:

[0010] Step 2: Preparation of filled composite microcrystalline graphite particles:

[0011] Mixing microcrystalline graphite particles with an impregnating agent, allowing the impregnating agent to fill the pores of the microcrystalline graphite particles, and heating and carbonizing to form filled composite microcrystalline graphite particles; the fixed carbon content of the impregnating agent is ≥14%; and the mass fraction of the impregnating agent used is ≥20%;

[0012] Step 3: Mixing and secondary crushing:

[0013] The filled composite microcrystalline graphite particles are crushed and sieved to obtain filled composite microcrystalline graphite particle powder, and the filled composite microcrystalline graphite particle powder is then heated, kneaded, cooled, crushed, and sieved to obtain secondary powder; the binder is coal tar pitch, and the quinoline insoluble content is ≥5%;

[0014] Step 4: Molding and calcining:

[0015] The secondary powder is molded into an embryo by isostatic pressing, and then calcined to 800-1000°C to obtain a primary calcined product, wherein the volume density of the primary calcined product is ≥1.70 g / cm 3 Directly proceed to step 5 or place the once calcined product in the impregnating agent described in step 2, and then perform a second calcination to obtain a bulk density ≥ 1.80g / cm 3 Secondary roasted products;

[0016] Step 5: Graphitization:

[0017] The primary calcined product or the secondary calcined product is graphitized at 2500-3000° C. using a high temperature graphitization furnace to obtain microcrystalline graphite-based isostatic graphite.

[0018] As a further improvement, the specific steps for preparing microcrystalline graphite particles in step 1 are as follows:

[0019] The microcrystalline graphite with a fixed carbon content of ≥98% and a porosity of 20-30% is placed in an Acheson furnace for purification. In the first stage, the temperature is raised to 1800-2000°C at a heating rate of 0.5-2°C / min, and freon is introduced for purification for 0.5-2h. In the second stage, the temperature is raised to 2000-2200°C, and chlorine is introduced for purification for 1-5h. In the third stage, the temperature is raised to 2600-2800°C, and the temperature is kept for 1-5h. The purified microcrystalline graphite is cooled with the furnace to obtain the purified microcrystalline graphite. The purified microcrystalline graphite is crushed by a mechanical crusher to obtain microcrystalline graphite particles. The microcrystalline graphite particles have a fixed carbon content of greater than 99.995%, a porosity of ≥30%, an average pore size of 35-45nm, and a particle size D 50 ≤20μm.

[0020] As a further improvement, the impregnating agent in step 2 is impregnating asphalt or impregnating resin, and the specific features are as follows:

[0021] The impregnating asphalt is coal tar with a softening point of 40-120°C, a quinoline insoluble content of ≤2%, and a fixed carbon content of 22%-36%; the impregnating resin is prepared by dissolving at least one of phenolic resin, polyimide resin or COPNA resin in anhydrous ethanol, the mass ratio of the resin to anhydrous ethanol is 30-70:70-30, and the fixed carbon content of the impregnating resin solution is 14-33%.

[0022] As a further improvement, in the preparation method of the composite microcrystalline graphite particles filled in step 2, when the impregnating agent is impregnating asphalt, the specific steps are as follows:

[0023] Liquid impregnation asphalt at a temperature of 150-200°C is added to microcrystalline graphite particles, wherein the mass ratio of microcrystalline graphite particles to liquid impregnation asphalt is 60-80:20-40, and negative pressure, normal pressure or pressurized impregnation is performed at a pressure of -0.1-1MPa, the impregnation temperature is 150-200°C, and heating is stopped after constant temperature stirring for 2-5 hours, and the particles are taken out after cooling to obtain the impregnated microcrystalline graphite particles; the heating carbonization step is: heating the impregnated microcrystalline graphite particles to 800-1000°C at a heating rate of 1-5°C / min to carbonize the coal tar in the pores of the microcrystalline graphite, thereby completing the preparation of the filled composite microcrystalline graphite particles.

[0024] As a further improvement, in the preparation method of the composite microcrystalline graphite particles filled in step 2, when the impregnating agent is an impregnating resin, the specific steps are as follows:

[0025] Add an impregnation resin solution to microcrystalline graphite particle powder, wherein the mass ratio of the microcrystalline graphite powder to the impregnation resin solution is 60-80:20-40, perform negative pressure, normal pressure or pressurized impregnation at a pressure of -0.1-1MPa, take out after stirring at room temperature for 2-5 hours, dry at 70°C in a blast drying oven for 3-8 hours, and then take out to obtain the impregnated microcrystalline graphite powder; the heating carbonization step comprises: heating the impregnated microcrystalline graphite powder to 800-1000°C at a heating rate of 1-5°C / min to carbonize the resin in the microcrystalline graphite pores, and completing the preparation of the filled composite microcrystalline graphite particles.

[0026] For further improvement, the specific steps of step three are as follows:

[0027] The composite microcrystalline graphite particle powder is mixed with the molten binder asphalt in a mass ratio of 7:3 in a kneader at a kneading temperature of 180-200°C. After kneading for 2-5 hours, the mixture is taken out and cooled. The cooled kneaded paste is crushed for the second time and passed through a 100-mesh standard sieve to obtain secondary powder. The binder asphalt is coal tar asphalt with a softening point of 100-130°C.

[0028] As a further improvement, in step 4, the specific steps of forming and calcining are as follows:

[0029] The secondary powder is loaded into a silicone rubber mold, and then the silicone rubber mold is placed in a cold isostatic press for molding. The pressurization rate during molding is 200MPa / min, the maximum molding pressure is 100-250MPa, and the pressure is maintained for 5-15min to obtain a green product; the green product obtained after molding is carbonized in a calcining furnace, and the green product is calcined to 800-1000°C at an average heating rate of 0.37°C / min in a nitrogen atmosphere, and kept warm for 1-2h. After cooling with the furnace, it is taken out to obtain a primary calcined product.

[0030] As a further improvement, in step 4, the specific steps of impregnation and secondary roasting are as follows:

[0031] The primary calcined product is placed in an impregnation tank filled with impregnating asphalt, the temperature is raised to 180-200°C, and the impregnation tank is evacuated at the same time. The pressure is maintained at 0.2 atmospheres for 10-30 minutes, and then the pressure is increased to 5-8MPa, and the pressure is maintained for impregnation for 1-2 hours. After impregnation, the impregnated sample is calcined in a calcination furnace, and heated to 800-1000°C at a heating rate of 0.5°C / min in a nitrogen atmosphere, and calcined for 1-2 hours to obtain a secondary calcined product.

[0032] As a further improvement, in step 5, the specific method of graphitization is as follows:

[0033] The calcined product is placed in a high-temperature graphitization furnace for graphitization, heated to 2500-3000° C. at a heating rate of 10-30° C. / min in an argon atmosphere, and kept warm for 0.5-2 hours to obtain microcrystalline graphite-based isostatic graphite.

[0034] Compared with the prior art, the present invention has the following obvious advantages:

[0035] 1. Controllable filling of microcrystalline graphite pores

[0036] The present invention realizes controllable filling of microcrystalline graphite pores by controlling the type and amount of the impregnating agent, so that the microcrystalline graphite retains certain pores while improving the strength and thermal conductivity of the microcrystalline graphite particles.

[0037] 2. The performance of microcrystalline graphite-based isostatic graphite can be adjusted

[0038] By selecting different types of impregnating agents and adjusting the filling degree of microcrystalline graphite pores, the mechanical properties and thermal expansion properties of microcrystalline graphite-based isostatic graphite can be regulated. When asphalt is used as the impregnating agent, the strength of microcrystalline graphite-based isostatic graphite can be improved while retaining a low thermal expansion coefficient. When resin solution is used as the impregnating agent, the improvement in the strength of microcrystalline graphite-based isostatic graphite is more significant.

[0039] 3. High strength of microcrystalline graphite-based isostatic graphite

[0040] Since the pores of microcrystalline graphite are filled, the strength of microcrystalline graphite particles is significantly improved compared with unfilled microcrystalline graphite particles, so that the flexural strength of the prepared microcrystalline graphite-based isostatic graphite can reach more than 40MPa, which is better than the isostatic graphite prepared from unfilled microcrystalline graphite.

[0041] 4. High thermal conductivity of microcrystalline graphite-based isostatic graphite

[0042] Since the pores of microcrystalline graphite are filled, the graphite crystallites in the microcrystalline graphite are connected by the impregnated asphalt-derived coke, which weakens the phonon-interface scattering, thereby improving the thermal conductivity of microcrystalline graphite-based isostatic graphite. When asphalt is used as the impregnating agent, the thermal conductivity of microcrystalline graphite-based isostatic graphite can reach more than 95W / mK, which is significantly better than the 70-80W / mK of isostatic graphite prepared from unfilled microcrystalline graphite.

[0043] 5. Low thermal expansion coefficient of microcrystalline graphite-based isostatic graphite

[0044] The present invention controls the filling of the pores of microcrystalline graphite, reduces the porosity and average pore size of microcrystalline graphite, and retains some pores, which can still effectively buffer the thermal expansion of graphite in the c-axis direction. Therefore, the prepared microcrystalline graphite-based isostatic graphite maintains a low thermal expansion coefficient of only 2.9-3.5×10 -6 / K, significantly better than coke-based isostatic graphite. Description of the drawings:

[0045] Figure 1 The X-CT three-dimensional reconstruction results of microcrystalline graphite, where (a) is the overall pore structure of microcrystalline graphite, (b) is the open pore structure of microcrystalline graphite, and (c) is the closed pore structure of microcrystalline graphite. It is obvious that the open pores in microcrystalline graphite are the main pores, exceeding 80% of the total pore volume, which is conducive to the filling of the microcrystalline graphite pores by the impregnant, and is the prerequisite for the implementation of the present invention.

[0046] Figure 2The TEM images of microcrystalline graphite are shown, where (a) is the raw material of microcrystalline graphite, in which the graphite microcrystals are disorderly stacked to form a large number of pores, and (b) is the TEM image of microcrystalline graphite impregnated with pitch and carbonized. It can be seen that the pores in the microcrystalline graphite are filled with the derivative coke formed by the carbonization of pitch, and the particle porosity and pore size are significantly reduced, while some pores are still retained. Therefore, by changing the filling degree of the internal pores of microcrystalline graphite, the strength, thermal expansion coefficient, thermal conductivity and other properties of graphite products can be regulated to obtain the required design performance.

[0047] Figure 3 The specific process route of the present invention is shown. Specific implementation method:

[0048] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0049] Example 1

[0050] This embodiment is a relatively optimized embodiment, using a low softening point impregnation asphalt, through the method of pressurized impregnation of ultrafine microcrystalline graphite powder, to prepare filled composite microcrystalline graphite particles, the specific method is as follows:

[0051] Step 1: Preparation of microcrystalline graphite particles

[0052] Microcrystalline graphite with a fixed carbon content of ≥98% and a porosity of 28.5% is used as raw material.

[0053] The above-mentioned microcrystalline graphite raw material is placed in an Acheson furnace for purification. In the first stage, the temperature is raised to 1900°C at a heating rate of 1°C / min, and freon is introduced for purification for 1 hour. In the second stage, the temperature is raised to 2100°C, chlorine is introduced, and purification is carried out for 5 hours. In the third stage, the temperature is raised to 2800°C, and the temperature is kept for 5 hours. The furnace is cooled to obtain purified microcrystalline graphite with a fixed carbon content greater than 99.995%, a porosity increase of 40.3%, and an ash content less than 50ppm. Subsequently, the above-mentioned purified microcrystalline graphite is crushed by a VT-300 mechanical crusher to obtain a high-purity ultrafine microcrystalline graphite particle powder, and its D 50 The average pore size is 5.8 μm, the porosity is 34.5%, the average pore size is 40.6 nm, and the specific surface area is 9.12 m 2 / g, relevant data are shown in Table 1.

[0054] Step 2: Preparation of filled composite microcrystalline graphite particles

[0055] Add liquid impregnation asphalt at a temperature of 200°C to the ultrafine microcrystalline graphite powder, wherein the mass ratio of microcrystalline graphite powder to liquid coal tar is 3:2, the QI content of the impregnation asphalt is 0.5%, the softening point is 80°C, and the fixed carbon content is 22%. Perform pressure impregnation at a pressure of 1MPa, the impregnation temperature is 200°C, and the heating is stopped after constant temperature stirring for 2h. Take it out after cooling to obtain the impregnated microcrystalline graphite powder. Use a roasting furnace to carbonize the impregnated powder. In a nitrogen atmosphere, heat it to 1000°C at a heating rate of 5°C / min to carbonize the coal tar in the pores of the microcrystalline graphite to obtain filled composite microcrystalline graphite particles with a porosity of 29.6%, an average pore size of 32.9nm, and a specific surface area of ​​5.12m 2 / g, relevant data are shown in Table 2.

[0056] Step 3: Mixing and secondary crushing

[0057] The above-mentioned composite microcrystalline graphite particles were crushed by a small mechanical crusher, and the obtained powder was passed through a 100-mesh standard sieve to obtain D 50 The invention discloses a composite microcrystalline graphite particle powder having a particle size of 28.7 μm; adding 3.5 kg of the composite microcrystalline graphite particle powder into a kneader, preheating the mixture at 180° C. for 0.5 h, then adding 1.5 kg of molten coal tar having a softening point of 114° C. and a QI content of 7.8%, kneading the mixture at 180° C. for 2 h, cooling the mixture and obtaining a kneaded paste; using a mechanical pulverizer to perform secondary pulverization on the cooled kneaded paste, and passing the obtained powder through a 100-mesh standard sieve to obtain secondary powder for subsequent molding.

[0058] Step 4: Forming and Firing

[0059] The secondary powder was loaded into a silicone rubber mold, and then placed in a cold isostatic press for molding. The mold was pressurized to 150 MPa at a pressurization rate of 200 MPa / min, and the mold was taken out after holding the pressure for 10 minutes to obtain a raw product. The raw product was carbonized in a calcining furnace, and the raw product was calcined to 1000°C at an average heating rate of 0.37°C / min in a nitrogen atmosphere, and kept warm for 2 hours, with a total time of about 45 hours. The mold was taken out after cooling with the furnace to obtain a bulk density ≥1.70 g / cm 3 A once-baked product.

[0060] Step 5: Graphitization

[0061] The calcined samples were graphitized in a high-temperature graphitization furnace. Under an argon atmosphere, they were first heated to 1000°C at a heating rate of 30°C / min, and then heated to 3000°C at a heating rate of 10°C / min and kept at that temperature for 0.5 h.

[0062] The microcrystalline graphite-based isostatic graphite prepared by the above method has a volume density of 1.75 g / cm 3 , flexural strength 41.6MPa, thermal expansion coefficient 3.1×10 -6 / K, isotropy is 1.02, thermal conductivity is 103.7W / mK, boron equivalent is 0.5ppm, and related data are shown in Table 3.

[0063] In this embodiment, the porosity and average pore size of the filled composite microcrystalline graphite particles are significantly reduced compared with the unimpregnated ultrafine microcrystalline graphite particles.

[0064] Example 2

[0065] This embodiment is basically the same as Embodiment 1, except that the basic properties of the impregnating asphalt used are different.

[0066] In this embodiment, an impregnation asphalt with a high softening point is used to prepare filled composite microcrystalline graphite particles by pressurized impregnation of ultrafine microcrystalline graphite powder; specifically, in step two, the impregnation asphalt has a QI content of 2%, a softening point of 115°C, and a fixed carbon content of 36%.

[0067] The porosity of the prepared filled composite microcrystalline graphite particles is 24.1%, the average pore diameter is 28.7nm, and the specific surface area is 4.31m 2 / g, related data are shown in Table 2; the microcrystalline graphite-based isostatic graphite prepared using the filled composite microcrystalline graphite particles has a volume density of 1.78g / cm 3 , flexural strength 46.1MPa, thermal expansion coefficient 3.5×10 -6 / K, isotropy is 1.01, thermal conductivity is 111.7W / mK, boron equivalent is 0.6ppm, and related data are shown in Table 3.

[0068] Compared with Example 1, the porosity and average pore size of the composite microcrystalline graphite particles filled in this example are lower, indicating that the high solid softening point asphalt has a stronger filling effect on the pores than the low softening point asphalt; thanks to the improvement in the pore filling effect of the aggregate, the flexural strength and thermal conductivity of the microcrystalline graphite-based isostatic graphite prepared in this example are higher than those in Example 1, and the thermal expansion coefficient does not change much compared with Example 1; this shows that by controlling the basic properties of the impregnating asphalt, it is possible to control the pore structure of the filled composite microcrystalline graphite particles, thereby controlling the mechanical properties and thermal expansion properties of the isostatic graphite, showing that the present invention has the characteristics of preparing microcrystalline graphite-based isostatic graphite with controllable structure and performance.

[0069] Example 3

[0070] This embodiment is basically the same as Embodiment 2, and the only difference is the difference in the impregnation pressure.

[0071] In this embodiment, the same high softening point impregnation asphalt as in Example 2 is used to prepare filled composite microcrystalline graphite particles by the method of negative pressure impregnation of ultrafine microcrystalline graphite powder; specifically, in step 2, negative pressure impregnation is carried out at a pressure of -0.1MPa, and heating is stopped after constant temperature stirring at 200°C for 2 hours. After taking out the powder, the impregnated microcrystalline graphite powder can be obtained.

[0072] The porosity of the prepared filled composite microcrystalline graphite particles is 27.2%, the average pore diameter is 31.7nm, and the specific surface area is 4.92m 2 / g, related data are shown in Table 2; the microcrystalline graphite-based isostatic graphite prepared using the filled composite microcrystalline graphite particles has a volume density of 1.76g / cm 3 , flexural strength 43.2MPa, thermal expansion coefficient 3.2×10 -6 / K, isotropy is 1.02, thermal conductivity is 106.6W / mK, boron equivalent is 0.6ppm, and related data are shown in Table 3.

[0073] Compared with Example 2, the porosity and average pore size of the composite microcrystalline graphite particles filled in this example are higher, indicating that the filling effect of negative pressure impregnation on the pores is worse than that of pressurized impregnation; the flexural strength, thermal expansion coefficient and thermal conductivity of the microcrystalline graphite-based isostatic graphite prepared in this example are all lower than those in Example 2.

[0074] Example 4

[0075] This embodiment is basically the same as embodiment 2, the only difference being the amount of impregnating asphalt used.

[0076] In this embodiment, an impregnation asphalt with a high softening point is used to prepare filled composite microcrystalline graphite particles by pressurized impregnation of ultrafine microcrystalline graphite powder; specifically, in step 2, liquid impregnation asphalt at a temperature of 200°C is added to the ultrafine microcrystalline graphite powder, wherein the mass ratio of microcrystalline graphite powder to liquid coal tar is 4:1, the impregnation asphalt has a QI content of 0.5%, a softening point of 80°C, and a fixed carbon content of 22%.

[0077] The porosity of the prepared filled composite microcrystalline graphite particles is 31.2%, the average pore diameter is 33.2nm, and the specific surface area is 5.21m 2 / g, related data are shown in Table 2; the microcrystalline graphite-based isostatic graphite prepared using the filled composite microcrystalline graphite particles has a volume density of 1.74g / cm 3 , flexural strength 40.1MPa, thermal expansion coefficient 3.0×10 -6 / K, isotropy is 1.01, thermal conductivity is 101.9W / mK, boron equivalent is 0.5ppm, and related data are shown in Table 3.

[0078] Compared with Example 2, the porosity and average pore size of the composite microcrystalline graphite particles filled in this example are higher, indicating that the amount of impregnating agent used is low, resulting in insufficient filling of the pores; the flexural strength, thermal expansion coefficient and thermal conductivity of the microcrystalline graphite-based isostatic graphite prepared in this example are all lower than those in Example 2.

[0079] Example 5

[0080] This embodiment is basically the same as embodiment 2, except that the once-baked sample is impregnated.

[0081] In this embodiment, impregnation asphalt with a high softening point is used. By pressurized impregnation of ultrafine microcrystalline graphite powder, filled composite microcrystalline graphite particles are prepared. The filled composite microcrystalline graphite particles are used to prepare raw products, and primary calcination, impregnation and secondary calcination are performed; specifically, in step four, the primary calcined product is impregnated in an impregnation tank filled with impregnated coal tar, and the impregnation tank is vacuumed while the temperature is raised to 200°C, and the pressure is maintained at 0.2 atmospheres for 20 minutes. Subsequently, the pressure is increased to 8MPa, and the pressure is maintained for 2 hours. After impregnation, the product is calcined in a calcination furnace, and heated to 1000°C at a heating rate of 0.5°C / min in a nitrogen atmosphere and calcined for 2 hours to obtain a secondary calcined product.

[0082] The microcrystalline graphite-based isostatic graphite prepared by this method has a volume density of 1.83 g / cm 3 , flexural strength 49.2MPa, thermal expansion coefficient 3.9×10 -6 / K, isotropy is 1.02, thermal conductivity is 116.5W / mK, boron equivalent is 0.6ppm, and related data are shown in Table 3.

[0083] Compared with Example 2, this example makes the flexural strength, thermal expansion coefficient and thermal conductivity of the prepared microcrystalline graphite-based isostatic graphite higher than those in Example 2 by impregnating and densifying the once-fired sample.

[0084] Example 6

[0085] This embodiment is basically the same as Embodiment 1, except that the impregnating agent used is a resin impregnating agent.

[0086] In this embodiment, a phenolic resin solution with a low fixed carbon content is used to prepare filled composite microcrystalline graphite particles by pressurized impregnation of ultrafine microcrystalline graphite powder; specifically, in step 2, a phenolic resin solution is added to the ultrafine microcrystalline graphite powder, wherein the mass ratio of microcrystalline graphite powder to phenolic resin solution is 3:2, the solvent of the phenolic resin solution is ethanol, the mass ratio of phenolic resin to anhydrous ethanol is 3:7, and the fixed carbon content of the resin solution is 14%. Pressurized impregnation is performed under a pressure of 1MPa, and the mixture is taken out after stirring at room temperature for 2h, and dried at 70°C in a blast drying oven for 8h, and the impregnated microcrystalline graphite powder is obtained after being taken out. The impregnated powder is heated to 1000°C at a heating rate of 5°C / min to carbonize the resin in the pores of the microcrystalline graphite, thereby completing the preparation of filled composite microcrystalline graphite particles.

[0087] The porosity of the prepared filled composite microcrystalline graphite particles is 31.9%, the average pore diameter is 32.5nm, and the specific surface area is 5.23m 2 / g, related data are shown in Table 2; the microcrystalline graphite-based isostatic graphite prepared by using the filled composite microcrystalline graphite particles has a volume density of 1.75g / cm 3 , flexural strength 40.9MPa, thermal expansion coefficient 3.2×10 -6 / K, isotropy is 1.02, thermal conductivity is 89.4W / mK, boron equivalent is 0.4ppm, and related data are shown in Table 3.

[0088] Compared with Example 1, the porosity of the composite microcrystalline graphite particles filled in this embodiment is higher. This is because compared with the asphalt impregnant, the resin impregnant has a lower fixed carbon content, and therefore the pore filling effect is not as good as asphalt; due to the poor pore filling effect, the flexural strength of the microcrystalline graphite-based isostatic graphite obtained in this embodiment is slightly lower than that in Example 1; the resin-derived carbon has the characteristic of being difficult to graphitize, and it is difficult to form pores that can adjust the thermal expansion of the c-axis of graphite after graphitization, so the thermal expansion coefficient is slightly higher than that of Example 1; at the same time, the resin-derived carbon is easy to form a lower degree of graphitization, so that the thermal conductivity of this embodiment is lower than that of Example 1.

[0089] Example 7

[0090] This embodiment is basically the same as Embodiment 6, the only difference being that the basic properties of the resin impregnating agent used are different.

[0091] In this embodiment, a phenolic resin solution with a high fixed carbon content is used to prepare filled composite microcrystalline graphite particles by pressurized impregnation of ultrafine microcrystalline graphite powder; specifically, in step 2, the phenolic resin solution is added to the ultrafine microcrystalline graphite powder, wherein the mass ratio of the microcrystalline graphite powder to the phenolic resin solution is 3:2, the solvent of the phenolic resin solution is ethanol, the mass ratio of the phenolic resin to anhydrous ethanol is 7:3, and the fixed carbon content of the resin solution is 33%.

[0092] The porosity of the prepared filled composite microcrystalline graphite particles is 26.6%, the average pore diameter is 28.5nm, and the specific surface area is 4.90m 2 / g, related data are shown in Table 2; the microcrystalline graphite-based isostatic graphite prepared using the filled composite microcrystalline graphite particles has a volume density of 1.77g / cm 3 , flexural strength 43.1MPa, thermal expansion coefficient 3.5×10 -6 / K, isotropy is 1.01, thermal conductivity is 95.2W / mK, boron equivalent is 0.4ppm, and related data are shown in Table 3.

[0093] Compared with Example 6, the porosity and average pore size of the composite microcrystalline graphite particles filled in this example are lower, indicating that the filling effect of the resin solution with a high fixed carbon content on the pores is stronger than that of the resin solution with a low fixed carbon content; thanks to the improved pore filling effect of the aggregate, the flexural strength and thermal conductivity of the microcrystalline graphite-based isostatic graphite prepared in this example are higher than those in Example 6, and the thermal expansion coefficient is also improved compared with that in Example 6; this indicates that by controlling the basic properties of the impregnating resin, it is also possible to control the pore structure of the filled composite microcrystalline graphite particles, thereby regulating the mechanical properties and thermal expansion properties of the isostatic graphite.

[0094] Example 8

[0095] This embodiment is basically the same as embodiment 7, the only difference being the difference in the impregnation pressure.

[0096] In this embodiment, a phenolic resin solution with a high fixed carbon content is used to prepare filled composite microcrystalline graphite particles by the method of negative pressure impregnation of ultrafine microcrystalline graphite powder; specifically, in step 2, negative pressure impregnation is carried out at a pressure of -0.1 MPa, and the mixture is taken out after stirring at room temperature for 2 hours and dried at 70°C in a forced air drying oven for 5 hours to obtain the impregnated microcrystalline graphite powder.

[0097] The porosity of the prepared filled composite microcrystalline graphite particles is 29.2%, the average pore diameter is 30.8nm, and the specific surface area is 5.02m 2 / g, related data are shown in Table 2; the microcrystalline graphite-based isostatic graphite prepared using the filled composite microcrystalline graphite particles has a volume density of 1.75g / cm 3, flexural strength 41.2MPa, thermal expansion coefficient 3.3×10 -6 / K, isotropy is 1.02, thermal conductivity is 90.1W / mK, boron equivalent is 0.4ppm, and related data are shown in Table 3.

[0098] Compared with Example 7, the porosity and average pore size of the composite microcrystalline graphite particles filled in this example are higher, indicating that the filling effect of negative pressure impregnation on the pores is worse than that of pressurized impregnation; the flexural strength, thermal expansion coefficient and thermal conductivity of the microcrystalline graphite-based isostatic graphite prepared in this example are lower than those in Example 7; it is worth mentioning that due to the use of negative pressure impregnation, the solvent in the resin evaporates during the impregnation stage, which shortens the drying time of the microcrystalline graphite particles.

[0099] Example 9

[0100] This embodiment is basically the same as embodiment 7, the only difference being the amount of the resin impregnating agent used.

[0101] In this embodiment, a phenolic resin solution with a high fixed carbon content is used to prepare filled composite microcrystalline graphite particles by pressurized impregnation of ultrafine microcrystalline graphite powder; specifically, in step 2, the phenolic resin solution is added to the ultrafine microcrystalline graphite powder, wherein the mass ratio of the microcrystalline graphite powder to the phenolic resin solution is 4:1, the solvent of the phenolic resin solution is ethanol, the mass ratio of the phenolic resin to anhydrous ethanol is 7:3, and the fixed carbon content of the resin solution is 33%.

[0102] The prepared filled composite microcrystalline graphite particles have a porosity of 32.6%, an average pore diameter of 32.9 nm, and a specific surface area of ​​5.45 m 2 / g, related data are shown in Table 2; the microcrystalline graphite-based isostatic graphite prepared using the filled composite microcrystalline graphite particles has a volume density of 1.74g / cm 3 , flexural strength 40.1MPa, thermal expansion coefficient 3.1×10 -6 / K, isotropy is 1.02, thermal conductivity is 87.5W / mK, boron equivalent is 0.4ppm, and related data are shown in Table 3.

[0103] Compared with Example 7, the porosity and average pore size of the composite microcrystalline graphite particles filled in this example are higher, indicating that the amount of impregnating agent used is low, resulting in insufficient filling of the pores; the flexural strength, thermal expansion coefficient and thermal conductivity of the microcrystalline graphite-based isostatic graphite prepared in this example are all lower than those in Example 7.

[0104] The above embodiments are only some specific implementation methods of the present invention and are not intended to be limitations of the present invention. Any simple improvements and replacements made thereto are within the protection scope of the present invention.

[0105] Comparative Example 1

[0106] In this comparative example, ultrafine microcrystalline graphite powder is used as aggregate, and a conventional preparation method is used to prepare microcrystalline graphite-based isostatically pressed graphite. The specific method is as follows:

[0107] Step 1: Preparation of microcrystalline graphite particles

[0108] Using microcrystalline graphite with a fixed carbon content of more than 98% and a porosity of 28.5% as a raw material, high-purity ultrafine microcrystalline graphite particle powder is prepared through purification, crushing and other steps. The preparation method is the same as step 1 in Example 1. The obtained high-purity ultrafine microcrystalline graphite particle powder D 50 The average pore size is 5.8 μm, the porosity is 34.5%, the average pore size is 40.6 nm, and the specific surface area is 9.12 m 2 / g, relevant data are shown in Table 1.

[0109] Step 2: Mixing and secondary crushing

[0110] In a kneader, 3.5 kg of the above-mentioned ultrafine microcrystalline graphite powder and 1.5 kg of molten coal tar were kneaded at 180°C for 2 hours, and the softening point of the coal tar was 114°C; a small mechanical pulverizer was used to perform secondary pulverization on the cooled kneaded paste, and the obtained powder was sieved through a 100-mesh standard sieve to obtain secondary powder for molding.

[0111] Step 3: Forming and Firing

[0112] The secondary powder was isostatically pressed in a rubber mold at a molding pressure of 150 MPa, and the green body was taken out after holding the pressure for 10 minutes. The green product was baked in a baking furnace. In a nitrogen atmosphere, the green product was carbonized to 1000°C at an average heating rate of 0.37°C / min, and kept warm for 2 hours, a total time of about 45 hours, and the baked product was obtained after cooling in the furnace.

[0113] Step 4: Graphitization

[0114] The calcined product was graphitized in a high-temperature graphitization furnace, heated to 1000°C at a heating rate of 30°C / min under an argon atmosphere, and then heated to 3000°C at a heating rate of 10°C / min and kept at that temperature for 0.5h to obtain the final microcrystalline graphite-based isostatic graphite; the obtained microcrystalline graphite-based isostatic graphite had a volume density of 1.70g / cm 3 , flexural strength 26.2MPa, thermal expansion coefficient 2.9×10 -6 / K, isotropy is 1.02, thermal conductivity is 72.3W / mK, boron equivalent is 0.5ppm, and related data are shown in Table 3.

[0115] By comparing the basic properties of the microcrystalline graphite-based isostatic graphite prepared in this comparative example with those of the embodiment, it can be seen that the isostatic graphite prepared with filled composite microcrystalline graphite particles as aggregate significantly improves the density, flexural strength and thermal conductivity of the microcrystalline graphite-based isostatic graphite while retaining the low thermal expansion characteristics.

[0116] Comparative Example 2

[0117] This comparative example is basically the same as comparative example 1, except that the raw material used is petroleum coke.

[0118] In this comparative example, domestic calcined petroleum coke particles are used as raw materials, and petroleum coke powder is obtained after purification and crushing, and the petroleum coke powder is used as aggregate to prepare isostatic graphite; specifically, in step 1, the domestic calcined petroleum coke particles are placed in an Acheson furnace for purification, and the purification process is the same as in Example 1, and then the purified petroleum coke is crushed by a VT-300 mechanical crusher to obtain high-purity petroleum coke particle powder, wherein D 50 The porosity is 23.1%, the average pore size is 132.3 nm, and the specific surface area is 2.12 m 2 / g, relevant data are shown in Table 1.

[0119] The isostatic graphite prepared using the above petroleum coke powder as aggregate has a bulk density of 1.66 g / cm 3 , flexural strength 31.1MPa, thermal expansion coefficient 5.6×10 -6 / K, isotropy is 1.05, thermal conductivity is 106.2W / mK, boron equivalent is 0.8ppm, and related data are shown in Table 3.

[0120] By comparing the basic properties of the microcrystalline graphite-based isostatic graphite prepared in this comparative example with those of the embodiment, it can be seen that the isostatic graphite prepared with filled composite microcrystalline graphite particles as aggregate has the characteristics of low thermal expansion, high flexural strength and high thermal conductivity, indicating that filled composite microcrystalline graphite particles are more advantageous in preparing high-performance isostatic graphite.

[0121] Comparative Example 3

[0122] This comparative example is basically the same as comparative example 2, except that the single-baked sample is subjected to an impregnation densification treatment.

[0123] In this comparative example, domestic calcined petroleum coke particles are used as raw materials, and petroleum coke powder is obtained after purification and crushing, and the petroleum coke powder is used as aggregate to prepare isostatic graphite. During the preparation process, the first roasted sample is impregnated once and roasted twice; specifically, in step four, the first roasted product is impregnated in an impregnation tank filled with impregnated coal tar, and the impregnation tank is heated to 200°C and evacuated at 0.2 atmospheres for 20 minutes. Subsequently, the pressure is increased to 8MPa and the pressure is maintained for 2 hours. After impregnation, a roasting furnace is used for roasting, and in a nitrogen atmosphere, it is heated to 1000°C at a heating rate of 0.5°C / min and roasted for 2 hours to obtain a secondary roasted product.

[0124] The isostatic graphite prepared by the above method has a bulk density of 1.76 g / cm 3 , flexural strength 46.1MPa, thermal expansion coefficient 5.9×10 -6 / K, isotropy is 1.04, thermal conductivity is 111.3W / mK, boron equivalent is 0.9ppm, and related data are shown in Table 3.

[0125] In this comparative example, the density of the isostatic graphite is made basically consistent with that of the embodiment through multiple impregnations. Although the isostatic graphite obtained in this comparative example has high flexural strength and thermal conductivity, its preparation process is complicated and its thermal expansion coefficient is significantly higher than that of the embodiment, which further illustrates the advantages of filled composite microcrystalline graphite particles in the preparation of high-performance isostatic graphite.

[0126] Table 1 Basic properties of the treated aggregates in each embodiment and comparative example

[0127]

[0128] Table 2 Basic properties of composite microcrystalline graphite particles filled in each embodiment

[0129]

[0130] 1. Comparing the basic properties of microcrystalline graphite particles in Table 1 and Table 2, it can be seen that the porosity and average pore size of microcrystalline graphite particles can be effectively reduced by impregnating microcrystalline graphite powder;

[0131] 2. When asphalt is used as the impregnating agent, the filling effect of high softening point asphalt on the pores of microcrystalline graphite is better than that of low softening point asphalt, because high softening point asphalt has a higher carbon yield;

[0132] 3. When using resin solution as impregnating agent, the resin with high fixed carbon content has better effect on filling the pores of microcrystalline graphite, also due to its higher carbon yield;

[0133] 4. By changing the type and basic properties of the impregnating agent, the pores of microcrystalline graphite particles can be filled in a controlled manner; 5. Compared with negative pressure impregnation, pressure impregnation has a better pore filling effect;

[0134] Table 3 Properties of isostatic pressing obtained in various embodiments and comparative examples

[0135]

[0136]

[0137] 1. According to the basic properties of isostatic graphite in the examples and comparative examples in Table 3, the physical properties of microcrystalline graphite-based isostatic graphite can be regulated by adjusting the pore structure of microcrystalline graphite;

[0138] 2. Compared with Comparative Example 1 without impregnation treatment, no matter what kind of impregnating agent is used, the flexural strength and thermal conductivity can be significantly improved. At the same time, due to the filling of pores, the thermal expansion coefficient of the microcrystalline graphite-based isostatic graphite increases slightly, but is still significantly lower than the petroleum coke-based isostatic graphite in Comparative Examples 2 and 3. The boron equivalent of the microcrystalline graphite-based isostatic graphite in the embodiment is also lower, which illustrates the advantages of this method in preparing high-performance isostatic graphite;

[0139] 3. Specifically, the use of asphalt as an impregnating agent can improve the flexural strength and thermal conductivity of microcrystalline graphite-based isostatic graphite while retaining the low thermal expansion characteristics of microcrystalline graphite;

[0140] 4. Using resin as an impregnating agent can also significantly improve the flexural strength and thermal conductivity of microcrystalline graphite-based isostatic graphite. The improvement effect is slightly worse than that of asphalt impregnating agent, but still better than the general preparation process in the comparative example;

[0141] 5. By comparing Examples 2 and 4, and Examples 7 and 9, it can be seen that when the impregnating agent content is low, the pores of the microcrystalline graphite may be incompletely filled, resulting in an insignificant increase in the strength of the isostatically pressed graphite product.

[0142] 6. By comparing Examples 2 and 5, it can be seen that the density and strength of the once-fired product can be significantly improved by impregnating the product.

[0143] 7. It is worth mentioning that the advantage of negative pressure impregnation is that it reduces the preparation time of filled composite particles. For asphalt impregnants, negative pressure impregnation during the impregnation stage can reduce the volatile matter in the asphalt, and can appropriately increase the heating rate during carbonization to improve production efficiency; for resin impregnants, negative pressure impregnation during the impregnation stage can accelerate the volatilization of solvents and reduce the drying time, thereby improving production efficiency.

Claims

1. A method for preparing microcrystalline graphite-based isostatic graphite, characterized in that: The steps include: Step 1: Preparation of microcrystalline graphite particles: Step 2: Preparation of filled composite microcrystalline graphite particles: Mixing microcrystalline graphite particles with an impregnating agent, allowing the impregnating agent to fill the pores of the microcrystalline graphite particles, and heating and carbonizing to form filled composite microcrystalline graphite particles; the fixed carbon content of the impregnating agent is ≥14%; and the mass fraction of the impregnating agent used is ≥20%; Step 3: Mixing and secondary crushing: The filled composite microcrystalline graphite particles are crushed and sieved to obtain filled composite microcrystalline graphite particle powder, and the filled composite microcrystalline graphite particle powder is then heated, kneaded, cooled, crushed, and sieved to obtain secondary powder; the binder is coal tar pitch, and the quinoline insoluble content is ≥5%; Step 4: Molding and calcining: The secondary powder is molded into a green product by isostatic pressing, and then calcined to 800-1000°C to obtain a primary calcined product, wherein the volume density of the primary calcined product is ≥1.70 g / cm 3 Directly proceed to step 5 or place the once calcined product in the impregnating agent described in step 2, and then perform a second calcination to obtain a bulk density ≥ 1.80g / cm 3 Secondary roasted products; Step 5: Graphitization: The primary calcined product or the secondary calcined product is graphitized at 2500-3000° C. using a high temperature graphitization furnace to obtain microcrystalline graphite-based isostatic graphite.

2. The method for preparing microcrystalline graphite-based isostatic graphite according to claim 1, characterized in that: The specific steps of preparing microcrystalline graphite particles in step 1 are as follows: The microcrystalline graphite with a fixed carbon content of ≥98% and a porosity of 20-30% is placed in an Acheson furnace for purification. In the first stage, the temperature is raised to 1800-2000°C at a heating rate of 0.5-2°C / min, and freon is introduced for purification for 0.5-2h. In the second stage, the temperature is raised to 2000-2200°C, and chlorine is introduced for purification for 1-5h. In the third stage, the temperature is raised to 2600-2800°C, and the temperature is kept for 1-5h. The purified microcrystalline graphite is cooled with the furnace to obtain the purified microcrystalline graphite. The purified microcrystalline graphite is crushed by a mechanical crusher to obtain microcrystalline graphite particles. The microcrystalline graphite particles have a fixed carbon content of greater than 99.995%, a porosity of ≥30%, an average pore size of 35-45nm, and a particle size D 50 ≤20μm.

3. The method for preparing microcrystalline graphite-based isostatic graphite according to claim 1, characterized in that: The impregnating agent in step 2 is impregnating asphalt or impregnating resin, and the specific characteristics are as follows: The impregnating asphalt is coal tar with a softening point of 40-120°C, a quinoline insoluble content of ≤2%, and a fixed carbon content of 22%-36%; the impregnating resin is prepared by dissolving at least one of phenolic resin, polyimide resin or COPNA resin in anhydrous ethanol, the mass ratio of the resin to anhydrous ethanol is 30-70:70-30, and the fixed carbon content of the impregnating resin solution is 14-33%.

4. The method for preparing microcrystalline graphite-based isostatic graphite according to claim 1, characterized in that: In the preparation method of the composite microcrystalline graphite particles filled in step 2, when the impregnating agent is impregnating asphalt, the specific steps are as follows: Liquid impregnation asphalt at a temperature of 150-200°C is added to microcrystalline graphite particles, wherein the mass ratio of microcrystalline graphite particles to liquid impregnation asphalt is 60-80:20-40, and negative pressure, normal pressure or pressurized impregnation is performed at a pressure of -0.1-1MPa, the impregnation temperature is 150-200°C, and heating is stopped after constant temperature stirring for 2-5 hours, and the particles are taken out after cooling to obtain the impregnated microcrystalline graphite particles; the heating carbonization step is: heating the impregnated microcrystalline graphite particles to 800-1000°C at a heating rate of 1-5°C / min to carbonize the coal tar in the pores of the microcrystalline graphite, thereby completing the preparation of the filled composite microcrystalline graphite particles.

5. The method for preparing microcrystalline graphite-based isostatic graphite according to claim 1, characterized in that: In the preparation method of the composite microcrystalline graphite particles filled in step 2, when the impregnating agent is an impregnating resin, the specific steps are as follows: Add an impregnation resin solution to microcrystalline graphite particle powder, wherein the mass ratio of the microcrystalline graphite powder to the impregnation resin solution is 60-80:20-40, perform negative pressure, normal pressure or pressurized impregnation at a pressure of -0.1-1MPa, take out after stirring at room temperature for 2-5 hours, dry at 70°C in a blast drying oven for 3-8 hours, and then take out to obtain the impregnated microcrystalline graphite powder; the heating carbonization step comprises: heating the impregnated microcrystalline graphite powder to 800-1000°C at a heating rate of 1-5°C / min to carbonize the resin in the microcrystalline graphite pores, and completing the preparation of the filled composite microcrystalline graphite particles.

6. The method for preparing microcrystalline graphite-based isostatic graphite according to claim 1, characterized in that: The specific steps of step three are as follows: The filled composite microcrystalline graphite particles are crushed and passed through a 100-150 mesh standard sieve to obtain filled composite microcrystalline graphite particle powder, and the filled composite microcrystalline graphite particle powder is kneaded with molten binder asphalt in a kneader at a mass ratio of 7:3, and the kneading temperature is 180-200°C. After kneading for 2-5 hours, the mixture is taken out and cooled, and the cooled kneaded paste is crushed for the second time and passed through a 100-150 mesh standard sieve to obtain secondary powder; the binder asphalt is coal tar asphalt, and the softening point is 100-130°C.

7. The method for preparing microcrystalline graphite-based isostatic graphite according to claim 1, characterized in that: In step 4, the specific steps of forming and calcining are as follows: The secondary powder is loaded into a silicone rubber mold, and then the silicone rubber mold is placed in a cold isostatic press for molding. The pressurization rate during molding is 200MPa / min, the maximum molding pressure is 100-250MPa, and the pressure is maintained for 5-15min to obtain a green product; the green product obtained after molding is carbonized in a calcining furnace, and the green product is calcined to 800-1000°C at an average heating rate of 0.37°C / min in a nitrogen atmosphere, and kept warm for 1-2h. After cooling with the furnace, it is taken out to obtain a primary calcined product.

8. The method for preparing microcrystalline graphite-based isostatic graphite according to claim 1, characterized in that: In the step 4, the specific steps of impregnation and secondary roasting are as follows: The primary calcined product is placed in an impregnation tank filled with impregnating asphalt, the temperature is raised to 180-200°C, and the impregnation tank is evacuated at the same time. The pressure is maintained at 0.2 atmospheres for 10-30 minutes, and then the pressure is increased to 5-8MPa, and the pressure is maintained for impregnation for 1-2 hours. After impregnation, the impregnated sample is calcined in a calcination furnace, and heated to 800-1000°C at a heating rate of 0.5°C / min in a nitrogen atmosphere, and calcined for 1-2 hours to obtain a secondary calcined product.

9. The method for preparing microcrystalline graphite-based isostatic graphite according to claim 1, characterized in that: In the step 5, the specific method of graphitization is as follows: The calcined product is placed in a high-temperature graphitization furnace for graphitization, heated to 2500-3000° C. at a heating rate of 10-30° C. / min in an argon atmosphere, and kept warm for 0.5-2 hours to obtain microcrystalline graphite-based isostatic graphite.

Citation Information

Patent Citations

  • Isotropic graphite product and preparation method thereof

    CN101654239A

  • Graphite negative electrode material, preparation method and lithium ion battery

    CN106169584A

Cited By

  • Lithium ion secondary battery, carbon material, preparation method of lithium ion secondary battery and carbon material, and electric device

    CN122091491A